REORIENTASI TEOLOGI ISLAM DARI TEOSENTRISME KE ANTROPOSENTRISME: ANALISIS KRITIS ATAS PEMIKIRAN HASAN HANAFI - Yuliani; Ali Amat; Saifullah SA (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article examines Hasan Hanafi’s reorientation of Islamic theology from a theocentric to an anthropocentric paradigm in response to intellectual stagnation and the contemporary humanitarian crisis in the Muslim world. Critiquing classical Islamic theology for its excessive metaphysical orientation and lack of engagement with social realities, Hanafi proposes a humanistic approach that positions human beings as active subjects in interpreting and actualizing religious teachings. This study employs a qualitative library-based method supported by philosophical, hermeneutical, and critical analysis. The findings show that Hanafi’s anthropocentric paradigm is grounded in three major foundations: the phenomenology of consciousness, praxis-oriented dialectics, and contextual hermeneutics. Together, these frameworks form a praxis-based theology oriented toward justice, liberation, and human well-being. The article also highlights the strengths of Hanafi’s thought in bridging religion and modernity and enhancing Islam’s social relevance, while acknowledging potential problems such as the risk of reducing transcendence and epistemological ambiguity. Overall, Hanafi’s ideas offer a significant contribution to the development of a more humanistic, rational, and transformative Islamic theology capable of addressing contemporary challenges.